OFF-PUMP CORONARY ARTERY BYPASS GRAFTING : LITERATURE REVIEW - Yousif, Rizgar (My University, 2020)
Coronary artery bypass grafting (CABG) is a commonly used revascularization technique for coronary artery disease. In addition to traditional on-pump CABG (ONCABG) with cardiopulmonary bypass (CPB), the operation can be performed on a beating heart without CPB and with no need for cardiac arrest, a procedure often called off-pump coronary artery bypass grafting (OPCABG). Extracorporeal circulation, aortic cross-clamping and cardiac arrest in ONCABG predispose the body to inflammatory response, global myocardial damage, coagulation defects and ischemia- reperfusion injury. These are associated with low blood pressure, thrombosis, hyperthermia, tachycardia, leukocytosis and tissue edema which all have detrimental effects on the outcome of the surgery. In OPCABG, these complications were initially thought to be reduced. Especially high-risk patients seem to benefit from OPCABG when compared to conventional ONCABG as it decreases the risk for mortality and morbidity shortly after discharging. On the other hand, the risk of incomplete revascularization and poor graft patency are higher in OPCABG procedures and reoperation is more often needed. Thus, in the long term, the benefit of OPCABG is not as significant. In low- and mid-risk population undergoing OPCABG no significant benefit has been reported. In addition to mortality, the choice between the two is an issue of financial aspect, total hospital stay, risk of complications and the experience of the surgeon. Significant superiority to each other is yet to be proven. The choice between the two methods has still to be made individually for each patient undergoing CABG. The purpose of this review is to search and gather literature and articles related to OPCABG, shortly discuss the role of it in cardiothoracic surgery, consider financial and healthcare aspects, compare short- and long-term outcomes and list some of the major complications of the procedure. Finally, there is a summary of the pros and cons, and the literature-based conclusions. Articles related to OPCABG were searched on PubMed using search keywords myocardial revascularization or myocardial revascularization [Mesh] in combination with OPCAB or OPCABG or off-pump coronary artery bypass or coronary artery bypass, off-pump [Mesh]. Also, some basic information such as explanations of procedures, have been cited from organization websites and published articles related to cardiothoracic surgery.
Keywords: myocardial revascularization, off-pump coronary artery bypass grafting, OPCABG